Early Illustrations of Geste Antagoniste in Cervical and Generalized Dystonia. (21st September 2015) - Broussolle, Emmanuel; Laurencin, Chloé; Bernard, Emilien; Thobois, Stéphane; Danaila, Teodor; Krack, Paul
Background: Geste antagoniste, or sensory trick, is a voluntary maneuver that temporarily reduces the severity of dystonic postures or movements. We present a historical review of early reports and illustrations of geste antagoniste. Results: In 1894, Brissaud described this phenomenon in Paris in patients with torticollis. He noted that a violent muscular contraction could be reversed by a minor voluntary action. He considered the improvement obtained by what he called "simple mannerisms, childish behaviour or fake pathological movements" was proof of the psychogenic origin of what he named mental torticollis. This concept was supported by photographical illustrations of the patients. The term geste antagoniste was used by Brissaud's pupils, Meige and Feindel, in their 1902 monograph on movement disorders. Other reports and illustrations of this sign were published in Europe between 1894 and 1906. Although not mentioned explicitly, geste antagoniste was also illustrated in a case report of generalized dystonia in Oppenheim's 1911 seminal description of dystonia musculorum deformans in Berlin. Discussion: Brissaud-Meige's misinterpretation of the geste antagoniste unfortunately anchored the psychogenic origin of dystonia for decades. In New York, Herz brought dystonia back into the realm of organic neurology in 1944. Thereafter, it was given prominence by other authors, notably Fahn and Marsden in the 1970–1980s. Nowadays, neurologists routinely investigate for geste antagoniste when a dystonic syndrome is suspected, because it provides a further argument in favor of dystonia. The term alleviating maneuver was proposed in 2014 to replace sensory trick or geste antagoniste. This major sign is now part of the motor phenomenology of the 2013 Movement Disorder Society's classification of dystonia.